Arabic Language Education in Islamic Higher Education - Rahimadinullah, Muhammad Zahid 'Afifarrasyihab; Kholisin, Kholisin (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study examines the complex relationship between globalization and Arabic language education within Islamic Higher Education Institutions (IHEIs). This study employs a qualitative approach with library research methodology. Findings reveal that globalization presents dual impacts: challenges, including digital divides affecting 55% of rural Islamic institutions, the commodification of education threatening formative spiritual goals, and curriculum westernization often misaligned with classical literacy objectives; and opportunities through glocalization approaches integrating modern pedagogies with traditional goals. An analysis of successful programs at IIUM Malaysia, Gontor Indonesia, and Qatar Foundation identifies common success factors, including institutional vision, adequate resource allocation, qualified faculty, and the contextual adaptation of global practices to local needs. The study demonstrates that technology integration through blended learning, mobile applications, and open educational resources can enhance accessibility while maintaining pedagogical quality when implemented thoughtfully. Results show Arabic language education possesses strategic potential as a bridge between Islamic heritage preservation and global engagement through literacy-first approaches, culturally relevant materials, and positioning multilingual competence as an asset for global citizenship. This research contributes to the discourse on educational decolonization and heritage language revitalization, offering evidence-based recommendations for policymakers, institutions, educators, and researchers to enhance the quality, equity, and relevance of Arabic language education in the 21st century.